LEGAL ANALYSIS OF THE EFFECTIVENESS OF AUTOGATE USE AND PERSONAL DATA PROTECTION AT IMMIGRATION CHECKPOINTS (RESEARCH STUDY AT THE CLASS I SPECIAL IMMIGRATION OFFICE IN BATAM) - Bayu Saputra; Bachtiar Simatupang; Ramlan (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
The development of digital technology in immigration services has driven the modernization of inspection systems through the use of autogates, an automated system that processes biometric data to verify the identity of travelers. However, the use of this technology raises legal issues related to the protection of personal data, especially in the context of compliance with Law Number 27 of 2022 concerning Personal Data Protection (PDP Law).This study aims to analyze the legal regulations and assess the effectiveness of personal data protection implementation in the autogate system at the Class I Special Immigration Office TPI Batam.The research method used is a normative juridical and empirical juridical approach, with data collection techniques through literature review, interviews, and field observations. A sociological approach to law is employed to assess the awareness and compliance of officers and users regarding the right to privacy in the practice of using the autogate. The results of the study show that, normatively, the legal regulations for personal data protection are already adequate, but they have not yet been specifically implemented in the governance of autogate usage at immigration checkpoints. At the implementation level, various technical, legal, and sociological obstacles were found, such as limited understanding of the Personal Data Protection Law by officials, the absence of specific SOPs, and low public awareness of their rights as data subjects. Recommendations include the need to formulate technical regulations that integrate the principles of the Personal Data Protection Law into the operations of the autogate system, regular training for immigration officers on personal data protection, and public education to increase legal awareness regarding the use of technology-based immigration services.